Commitment to Diversity and Its Influence on Athletic Department Outcomes - George Cunningham (University of Kansas Libraries, 2008)
The purpose of this research was to propose a multidimensional construct of commitment to diversity, develop a questionnaire to measure the respective mindsets, and to consider outcomes of such commitment. In Study 1 (N = 199 undergraduate students), a questionnaire was developed and its validity evidence based internal structure supported through confirmatory factor analysis. Results from Study 2 (N = 593 NCAA Division II administrators) indicated that the factor structure of the commitment to diversity questionnaire was equivalent across sex and race. Finally, results from Study 3 (N = 911 administrators from 258 NCAA Division I athletic departments) indicated that the collective commitment mindsets of department personnel interacted with the diversity in the department to influence three departmental outcomes: attraction of a diverse fan base, employee satisfaction, and creativity. Results are discussed in terms of contributions to the literature.